Perilaku Kuat Geser Dinding Panel Dengan Perkuatan Diagonal Tulangan Baja - Bahri, Saiful, Muhammad Ujianto, ST., MT, Yenny Nurchasanah, S.T., M.T (2016)
In the development of technology we can make building that having excellence and advantage of them which can adjust needs, technical specifications and strength, and the implementation of rapid construction and nature friendly that can be compared with any building material in the present time, one of them is a wall panel or precast. The panel that light and strong by adding diagonal bracing for applied to the house with earthquake resistence. In this research there are two types of the wall panel 3 of the panel without reinforcement and 3 of the panel is reinforcement with diagonal renforcement steel with the same size 74 cm x 64 cm x 7cm . Testing of shear strength wall panel done by means of the provision of a burden on the upper end of the wall , granting burden observed every 5 kN until it reaches maximum load , observe the pattern of cracks and shifts that happened .The data obtained are a burden given up to maximum , fractured cracks pattern that occurs , and a wall panel shift occurring due to the provision of a burden .The result of research and discussion got that with a wall panel diagonal steel renforcement having a shear rigidity and shear strong better than the walls without reinforcement panel . The panel with bracing diagonal tulangan steel having stiffness of shear 4920,13 kN/m the wall without reinforcement panel just get stiffness of shear 2210,40 kN/m and the panel with reinforcement diagonal bracing steel has a shear strenght of 68,59 kN/m the wall without reinforcement panel just getting shear strenght of 45,10 kN/m. From these results prove that diagonal reinforcement able to enhance shear rigidity and strenght shear larger and reduce deflection happened .The panel with reinforcement diagonal bracing steel can be used as a substitute for conventional brick walls